Neonatal Myocardial Infarction: A Proposed Algorithm for Coronary Arterial Thrombus Management. (29th April 2022) - El-Sabrout, Hannah; Ganta, Srujan; Guyon, Peter; Ratnayaka, Kanishka; Vaughn, Gabrielle; Perry, James; Kimball, Amy; Ryan, Justin; Thornburg, Courtney D.; Tucker, Suzanne; Mo, Jun; Hegde, Sanjeet; et al.
Abstract : Background: Neonatal myocardial infarction is rare and is associated with a high mortality of 40% to 50%. We report our experience with neonatal myocardial infarction, including presentation, management, outcomes, and our current patient management algorithm. Methods: We reviewed all infants admitted with a diagnosis of coronary artery thrombosis, coronary ischemia, or myocardial infarction between January 2015 and May 2021. Results: We identified 21 patients (median age, 1 [interquartile range (IQR), 0.25–9.00] day; weight, 3.2 [IQR, 2.9–3.7] kg). Presentation included respiratory distress (16), shock (3), and murmur (2). Regional wall motion abnormalities by echocardiogram were a key criterion for diagnosis and were present in all 21 with varying degrees of depressed left ventricular function (severe [8], moderate [6], mild [2], and low normal [5]). Ejection fraction ranged from 20% to 54% (median, 43% [IQR, 34%–51%]). Mitral regurgitation was present in 19 (90%), left atrial dilation in 15 (71%), and pulmonary hypertension in 18 (86%). ECG was abnormal in 19 (90%). Median troponin I was 0.18 (IQR, 0.12–0.56) ng/mL. Median BNP (B-type natriuretic peptide) was 2100 (IQR, 924–2325) pg/mL. Seventeen had documented coronary thrombosis by cardiac catheterization. Seventeen (81%) were treated with intracoronary tPA (tissue-type plasminogen activator) followed by systemic heparin, AT (antithrombin), and intravenous nitroglycerin, and 4 (19%) were treated with systemic heparin, AT, and intravenous nitroglycerin alone. Nineteen of 21 recovered. One died (also had infradiaphragmatic total anomalous pulmonary venous return). One patient required a ventricular assist device and later underwent heart transplant; this patient was diagnosed late at 5 weeks of age and did not respond to tPA. Nineteen of 21 (90%) regained normal left ventricular function (ejection fraction, 60%–74%; mean, 65% [IQR, 61%–67%]) at latest follow-up (median, 6.8 [IQR, 3.58–14.72] months). Two of 21 (10%) had residual trivial mitral regurgitation. After analysis of these results, we present our current algorithm, which developed and matured over time, to manage neonatal myocardial infarction. Conclusions: We experienced a lower mortality rate for infants with neonatal infarction than that reported in the literature. We propose a post hoc algorithm that may lead to improvement in patient outcomes following coronary artery thrombus.